The influence of knowledge of tax regulations and service quality by tax officers controlling taxpayers' willingness to pay restaurant taxes with sanctions as a moderating variable (case study in Semarang city) - Fitria Rizkika Cahyarani; Achmad Badjuri (SEAN Institute, 2024)
The research aims to analyze various regulations regarding taxes, service quality, and sanctions that influence the willingness of individuals or business entitis to pay taxes. In this study, researcher uses primary data by using a questionnaire where consists of 110 respondents for the research. The sampling technique used by the researcher is purposive sampling technique. The analysis method uses simple regression analysis test and moderated regression analysis test. The result of the research states that tax knowledge regulation has a positive significant effect on the willingness to pay taxes, while service quality does not have influence on willingness to pay taxes. In the research, it shows that sanctions are able to moderate the correlation between tax knowledge regulation and service quality.